Legal review on termination of employment due to urgent misconduct - Wahyudin, Hari; Prawesthi, Wahyu; Amiq, Bachrul; Marwiyah, Siti (IHSA Institute, 2025)
The research problems formulated in this study are: 1) How does Indonesian law regulate employment termination due to urgent violations and what are the criteria for violations that can be considered urgent and serve as grounds for employment termination? 2) Does Decision No. 9/Pdt.Sus-PHI/2023/PN.Pal issued by the Industrial Relations Court of Palu District Court aligns with the applicable legal provisions? This study aims to analyze and understand the legal implications of employment termination due to urgent violations. This research employs normative legal methods using statutory, case, and comparative approaches. The norms under Article 52 paragraphs (2) and (3) of Government Regulation No. 35 of 2021 provide that employers may terminate employment contracts without prior notice based on Employment Agreements, Company Regulations, and Collective Labor Agreements. However, there is no clear definition or criteria regarding what constitutes an urgent violation as stipulated in the explanatory provisions of Article 52 paragraph (2) of Government Regulation No. 35 of 2021. This research not only makes theoretical contributions to the development of legal science, but also practical contributions to the world of labor. By clarifying the definition of “urgent violations,” proposing regulatory improvements, as well as providing recommendations for employers, workers, and the government, this research can be the basis for a more just and sustainable labor policy